(untitled) (Mustansiria Dental Journal, 2018)
The fear of uncontrolled bleeding often prompts medical practitioners to stop aspirin intake for seven to 10 days before any surgical procedure. This study was initiated to evaluate the effect of aspirin on bleeding in patients undergoing oral surgery. The study group consisted of 39 patients who were subjected to undergo dental extraction. All patients were receiving 100 milligrams of aspirin daily on a regular basis. Patients were randomly divided into two groups: those who stopped the aspirin therapy before the procedure and those who continued the aspirin therapy. One hour before the procedures, all patients underwent a bleeding time test. In addition, the amount of bleeding during the procedure was measured. The mean (± standard deviation) bleeding time was 1.8 ± 0.47 minutes for patients who stopped aspirin therapy one week before the procedure. For patients who continued aspirin therapy, the bleeding time was 3.1 ± 0.65 minutes. The difference was statistically significant (P = .004). However, both groups were within the normal bleeding time range, and in both groups, a local hemostatic method was sufficient to control bleeding. No episodes of uncontrolled intraoperative or postoperative bleeding were noted. Stopping of low-dose aspirin therapy is not a must before oral surgery. Local hemostasis is sufficient to control bleeding.